Corticosteroid status inﬂuences the volume of the rat cingulate cortex: a magnetic resonance imaging study - Cerqueira, João (2005)
Imbalances in the corticosteroid milieu result in reductions in hippocampal volume in humans and experimental rodents. The functional correlates of these changes include deﬁcits in cognitive performance and regulation of the hypothalamic–pituitary–adrenal axis. Since other limbic structures which are intricately connected with the hippocampal formation, also play an important role in behavioural and neuroendocrine functions, we here used magnetic resonance imaging (MRI) to analyse how two of these areas, the anterior cingulate and retrosplenial cortex, respond to chronic alterations of adrenocortical status: hypocortisolism (induced by adrenalectomy, ADX), normocortisolism (ADX with low-dose corticosterone replacement), and hypercortisolism (ADX with high-dose dexamethasone supplementation). Hypercortisolism was associated with a signiﬁcant reduction in the volume (absolute and normalized) of the left anterior cingulate gyrus as measured by MRI and conﬁrmed using classical histological methods; a similar trend was observed in the right anterior cingulate region. In contrast, hypercortisolism did not inﬂuence the volume of the adjacent retrosplenial cortex. The volumes of the anterior cingulate gyrus and retrosplenial cortex were unaffected by the absence of adrenocortical hormones. These ﬁndings are the ﬁrst to suggest that corticosteroid inﬂuences on the structure of the limbic system extend beyond the hippocampal formation, i.e., to fronto-limbic areas also.